Thermographic: a tool of aid in physical therapy diagnosis - literature review. - Santos, Maikon Gleibyson Rodrigues dos; Silva, Luiz Guilherme Cardoso da; Júnior, José Roberto de Souza; Lemos, Thiago Vilela; Matheus, João Paulo Chieregatto (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Maintaining body temperature by the human body occurs through the control of the autonomic nervous system in the cutaneous microcirculation, it is necessary for there to be effective in chemical reactions and consequent maintenance of homeostasis. The human body exhibits a thermal symmetry. When any asymmetry occurs relating the contralateral area, there are some evidences of a series of cases, ranging from an inflammatory process to neurovascular changes. Thermography makes the analysis of the temperature distribution on the surface of the skin, being a tool that can be used in assessment and diagnosis of such disorders, contributing to the evolution of the treatment of patients led to physiotherapy services. Objective: To investigate the importance of thermography as an adjunct diagnostic tool in physical therapy, showing its applicability. Method: This is a literature review using various electronic databases such as PubMed, Science Direct, Scopus, Web of Science and SciELO, by crossing the term thermography diagnosis and therapy. The sample consisted of 8 items. Results: Thermography proved a useful tool in the early diagnosis allowing the evaluation of local excessive friction prostheses muscle injury, occupational disorders, ischemic areas, and joint overloads beyond the initiation of an inflammatory process, which still showed no signs and symptoms classic, providing the physiotherapist take preventative measures and perform rapid and effective intervention. Conclusion: It can be concluded from the present review that thermography can be used as an excellent diagnostic tool for physical therapy because it is a non invasive method with no side effects, with good sensitivity and reliability.